The Effects of Community Policing on Complaints Against Officers - Kessler, David A. (Journal of quantitative criminology, 1999)
Between 1982 and 1989, the Houston Police Department was committed toforming partnerships with the community as part of its strategy to improvepolice service to the city. Using complaint data from the Internal AffairsDivisions of the Houston Police Department, this research examines whetherofficers assigned to areas of the city that implemented community policinghave fewer complaints than other officers. The results showed that officersworking in areas where community policing had been implemented receivedsignificantly fewer complaints than officers working in other areas. Anexception was complaints for criminal behavior, which increased. The resultssuggest that models of community policing that focus on creating communitypartnerships have the potential to reduce tension between the police and thepublic.